Public Participation in Constitutional Amendments with Deliberation Requirements in the Unamendability Framework: A Comparative Study - Nugraha, Xavier; Felicia, Stefania Arshanty; Hartono, Julienna (Jurnal Mulawarman Law Review, 2022)
From time to time, it is considered that Constitutional Amendments are lack of public participation and contains political aspects. Therefore, many nations regulate certain provisions to ensure that the Constitutional Amendments are merely for public order and welfare. One of the provision is the temporal unamendability. In the shape of deliberation requirements, which is essentially the involvement of the public in submitting constitutional amendments within a certain time limit. Indonesian Law doesn’t recognize the concept of deliberation requirements, therefore, the authors will analyze Sweden and South Korean Law, two countries that are also using civil law system and have regulated deliberation requirements in submitting constitutional amendments. This paper will discuss two problems: 1) the legal provisions for constitutional amendments in Indonesia, Sweden, and South Korea, and 2) the guarantee model for public participation in constitutional amendments using the deliberation requirements model. This paper uses legal research method, with a conceptual, statutory, and comparative approach. The results show that Sweden and South Korean Law have involved both the public and the Representative Body to determine wether constitutional amendment will be performed, meanwhile Indonesia hasn’t involve the public to vote for a constitutional amendments. Therefore, to guarantee public participation in constitutional amendments, the authors provide a model which include the public participation through vote or referendum to decide a constitutional amendments and a period of time to file for constitutional amendment.